2022
DOI: 10.1021/acsanm.2c03268
|View full text |Cite
|
Sign up to set email alerts
|

Review of MXene Nanosheet Composites for Flexible Pressure Sensors

Abstract: Recently, there has been a huge demand for flexible pressure sensors in various fields, including smart wearable textiles, health detection, and electronic skin. Flexible pressure sensors have been developed with high sensitivity, wide sensing range, rapid response time, and excellent cycling stability. Currently, emerging conductive materials include two-dimensional transition metal carbides and nitrides (MXenes). These materials have attracted immense attention in the field of flexible pressure sensors due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 139 publications
0
10
0
Order By: Relevance
“…48 The band at 1193 cm À1 was attributed to the C-O-H or C-N bond, 49 and the sulfur-oxygen bond appeared at 659.5 cm À1 . 44 According to the XPS data, these observed stretching vibrations demonstrate that the surface of SQDs is covered with functional groups related to sulfur, nitrogen, and oxygen.…”
Section: Characterization Of Sqdsmentioning
confidence: 98%
See 1 more Smart Citation
“…48 The band at 1193 cm À1 was attributed to the C-O-H or C-N bond, 49 and the sulfur-oxygen bond appeared at 659.5 cm À1 . 44 According to the XPS data, these observed stretching vibrations demonstrate that the surface of SQDs is covered with functional groups related to sulfur, nitrogen, and oxygen.…”
Section: Characterization Of Sqdsmentioning
confidence: 98%
“…Also, the binding energy peaks at 166.4 and 167.69 eV may be attributed to the SO 3 À (2p 2/3 ), SO 2 2À (2p 1/1 ) or SO 3 2À (2p 2/3 ). [42][43][44] The deconvoluted N 1s spectrum indicated binding energies of 399.88, 397.67 and 400.32 eV (Fig. 1d), which might correspond to the S-N, C-N and N-H functional groups, respectively.…”
Section: Characterization Of Sqdsmentioning
confidence: 99%
“…Wet-spinning, electrospinning, and coating are three widely examined textile processing processes that are currently being researched to generate MXene-mediated yarns, fibers, and textiles. 69 In order for MXene to perform its role as a codopant in numerous spinning solutions that contain polymers, it has been utilized as an efficient nanofiller and introduced into these solutions. The outcome is nanofibers that have several functions in contrast to pure polymeric spun fibers.…”
Section: Mxene-based Wearable Electronicsmentioning
confidence: 99%
“…[4] Researches has shown that compounding MXene nanosheets with graphene, carbon nanotubes, conductive polymers, and polymers could improve the shear viscosity of MXene dispersions, which contributes to the formation of macroscopic fibers. [5] The improvement in rheological properties can be attributed to the synergistic effect of the added materials with MXene nanosheets. [6,7] These added materials help to reduce the aggregation and stacking between the MXene nanosheets, allowing a more uniform and stable dispersion.…”
Section: Introductionmentioning
confidence: 99%